2013
DOI: 10.1016/j.yjmcc.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Roles of endothelial nitric oxide synthase (eNOS) and mitochondrial permeability transition pore (MPTP) in epoxyeicosatrienoic acid (EET)-induced cardioprotection against infarction in intact rat hearts

Abstract: We previously demonstrated that 11,12 and 14,15-epoxeicosatrienoic acids (EETs) produce cardioprotection against ischemia-reperfusion injury in dogs and rats. Several signaling mechanisms have been implicated in the cardioprotective actions of the EETs; however, their mechanisms remain largely elusive. Since nitric oxide (NO) plays a significant role in cardioprotection and EETs have been demonstrated to induce NO production in various tissues, we hypothesized that NO is involved in mediating the EET actions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 60 publications
0
21
0
1
Order By: Relevance
“…Although the downstream protective targets activated by STAT3 have not been systematically investigated, some research has reported that phosphorylation of STAT3 can activate downstream protective substrates, including Akt, eNOS, and GSK3β [18, 40]. STAT3, Akt and eNOS have been shown to inhibit opening of the mPTP during reperfusion [41-43], which can maintain mitochondrial membrane integrity and inhibit the activation of the mitochondrial apoptosis pathway. In our study, we indeed observed that RIPostC increased Akt and eNOS Ser1177 phosphorylation and that pretreatment with the JAK/STAT3 inhibitor AG490 attenuated the phosphorylation of STAT3 as well as the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the downstream protective targets activated by STAT3 have not been systematically investigated, some research has reported that phosphorylation of STAT3 can activate downstream protective substrates, including Akt, eNOS, and GSK3β [18, 40]. STAT3, Akt and eNOS have been shown to inhibit opening of the mPTP during reperfusion [41-43], which can maintain mitochondrial membrane integrity and inhibit the activation of the mitochondrial apoptosis pathway. In our study, we indeed observed that RIPostC increased Akt and eNOS Ser1177 phosphorylation and that pretreatment with the JAK/STAT3 inhibitor AG490 attenuated the phosphorylation of STAT3 as well as the phosphorylation of Akt and eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, EET-induced activation of K ATP channels seems to be cardioprotective and EETs can regulate cardiac electrophysiology and prevent the increase in intracellular Ca 2+ that is generally associated with ischemia-reperfusion injury (Batchu et al, 2012a). More recently, the cardioprotective effect of EETs administered prior to ischemia was attributed to the activation of the eNOS and increased NO production, whereas K ATP channel activation and the mitochondrial permeability transition pore were involved in the beneficial effects of the EETs when administered just prior to reperfusion (Gross et al, 2013). The actions of EETs in other organs, such as insulin secretion in pancreatic islets, may also be linked to K ATP channel activation (Sharoyko et al, 2007).…”
Section: B Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…For a more detailed mechanistic analysis, further studies using cell experiments in vitro are needed. The notion that EETs activate eNOS via phosphorylation is supported by previous studies in a number of biological systems [5,35,36]. MI/R injury is reduced in mice overexpressing eNOS, suggesting cardioprotection by eNOS [37][38][39].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 79%